Laparoscopic surgery in treatment of patients with endometrial cancer and obesity - A. I. Berishvili; K. P. Laktionov; T. M. Kochoyan; S. B. Polikarpova; N. V. Levkina (Опухоли женской репродуктивной системы, 2014)
The paper evaluates the role and place of laparoscopic surgery in treatment of patients with endometrial cancer and obesity. It describes the types of similar operations: laparoscopic hysterectomy ± pelvic lymphadenectomy. Overall and disease-free survival is reported to be the same with both laparoscopy and open surgery.